An Advanced Microstructural and Electrochemical Datasheet on 18650 Li-Ion Batteries with Nickel-Rich NMC811 Cathodes and Graphite-Silicon Anodes. Issue 14 (5th November 2020) - Heenan, T. M. M.; Jnawali, A.; Kok, M. D. R.; Tranter, T. G; Tan, C.; Dimitrijevic, A.; Jervis, R.; Brett, D. J. L.; Shearing, P. R.
Abstract : Cylindrical lithium-ion batteries are used across a wide range of applications from spacesuits to automotive vehicles. Specifically, many manufacturers are producing cells in the 18650 geometry i.e., a steel cylinder of diameter and length ca. 18 and 65 mm, respectively. One example is the LG Chem INR18650 MJ1 (nominal values: 3.5 Ah, 3.6 V, 12.6 Wh). This article describes the electrochemical performance and microstructural assembly of such cells, where all the under-pinning data is made openly available for the benefit of the wider community. The charge-discharge capacity is reported for 400 operational cycles via the manufacturer's guidelines along with full-cell, individual electrode coating and particle 3D imaging. Within the electrochemical data, the distinction between protocol transition, beginning-of-life (BoL) capacity loss, and prolonged degradation is outlined and, subsequently, each aspect of the microstructural characterization is broken down into key metrics that may aid in understanding such degradation (e.g., electrode assembly layers, coating thickness, areal loading, particle size and shape). All key information is summarized in a quick-access advanced datasheet in order to provide an initial baseline of information to guide research paths, inform experiments and aid computational modellers.